Could the Internet of Things Be Used to Enhance Student Nurses' Experiences in a Disaster Simulation? - Laplante, Nancy L.; Laplante, Phillip A.; Voas, Jeffrey M. (Online Journal of Nursing Informatics)
Disaster nursing gained interest after the terrorist attacks of September 11, 2001. Schools of nursing recognized the need to prepare future nurses to care for victims, and function as part of the interprofessional team for all stages of disasters. Challenges for nursing education have been to add this content to an already over-packed curriculum and demonstrate the importance to students who are very acute care-focused. Simulation has been one means to do this, with many schools investing much time and energy to create extensive disaster simulations. A recent undergraduate disaster simulation sparked an interest as to whether the Internet of Things (IoT) could be included to further challenge and engage students. The simulation was well received by students and faculty, and opportunities to collaborate with first responders provided a more realistic experience for students. Upon reflection, the authors wondered if the experience could be further enhanced with the use of technologies, such as the tracking of victims with a different system other than paper triage tags. IoT has promised to create many opportunities for enhancing human lives, and although IoT has gained in popularity, nursing has been slow to adopt these technologies, in particular with regard to undergraduate nursing education. The authors previously introduced a structured framework for specifying, designing and implementing healthcare applications in the IoT, and now build on this work for this paper. Disaster simulation could be an opening to introduce IoT in a meaningful way, thus highlighting the application of these technologies for future nurses.